2002
DOI: 10.1023/a:1016135410934
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study investigated cytotoxicity of cement fragments harvested from two prosthesis revisions by the MTT test using L929 fibroblasts and human osteoblasts. The results did not show any toxicity of the extracts prepared after 48 and 78 months implantation. We consider that no MMA monomer has been released from the cement fragments. Histological studies on undecalcified samples harvested around revising prosthesis from 11 patients were used to evaluate tissue reactions at the bone-cement interface after 2-168… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The monomer toxicity should disappear completely within four hours [3]. No monomer fragments are released after PMMA implantation, and no PMMA toxicity occurs after 48 and 78 months following surgical reconstruction [10]. …”
Section: Discussionmentioning
confidence: 99%
“…The monomer toxicity should disappear completely within four hours [3]. No monomer fragments are released after PMMA implantation, and no PMMA toxicity occurs after 48 and 78 months following surgical reconstruction [10]. …”
Section: Discussionmentioning
confidence: 99%
“…After the polymerization, usually 15 min, about 3-5% of the monomer remains, and decreases to 1-2% with time. The monomer toxicity should disappear within 4 h 12 . Lu, et al 12 (2002) did not found any toxicity of PMMA after 48 and 78 months of implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The monomer toxicity should disappear within 4 h 12 . Lu, et al 12 (2002) did not found any toxicity of PMMA after 48 and 78 months of implantation. In addition, the authors reported no MMA monomer released fragments after implantation.…”
Section: Discussionmentioning
confidence: 99%
“…By combining them with a nondegradable, high Tg monomer, such as methyl methacrylate, the Tg of the network was increased to ambient conditions [32]. The biodegradable crosslinkers have shown previous biocompatibility in vivo , and PMMA is well known to be biocompatible [3335]. In order for the PBAE-MMA network to have the same benefits of standard biodegradable polymers, it must elicit a favorable biological response, while also showing an increase in modulus during degradation.…”
Section: Introductionmentioning
confidence: 99%